Diplomacy - Kissinger, Henry (London Simon & Schuster Paperbacks, 1994)
Kissinger describes the ways in which the art of diplomacy and the balance of power created the world we live in.
Include Illustrations and Index
Keywords: Diplomacy -- United States -- Diplomatic relations